2012
DOI: 10.1089/ten.tea.2011.0657
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Impedes Hypertrophic Chondrogenesis of Human Multipotent Stromal Cells

Abstract: Within the field of bone tissue engineering, the endochondral approach to forming bone substitutes represents a novel concept, where cartilage will undergo hypertrophic differentiation before its conversion into bone. For this purpose, clinically relevant multipotent stromal cells (MSCs), MSCs, can be differentiated into the chondrogenic lineage before stimulating hypertrophy. Controversy exists in literature on the oxygen tensions naturally present during this transition in, for example, the growth plate. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 33 publications
4
68
0
Order By: Relevance
“…This was would suggest that relative levels of type X collagen production preimplantation are not necessarily predictive of the extent of endochondral bone formation in vivo. The more rapid degradation rate of the alginate in vivo is likely favoring vascularization and oxygen availability within this hydrogel, and subsequently driving hypertrophy [30,46].…”
Section: Discussionmentioning
confidence: 99%
“…This was would suggest that relative levels of type X collagen production preimplantation are not necessarily predictive of the extent of endochondral bone formation in vivo. The more rapid degradation rate of the alginate in vivo is likely favoring vascularization and oxygen availability within this hydrogel, and subsequently driving hypertrophy [30,46].…”
Section: Discussionmentioning
confidence: 99%
“…The multilineage potential of the cells that were cultured from the bone marrow aspirate was investigated by a three-way differentiation assay as previously described [19,28,29].…”
Section: Isolation Of Equine Chondrocytes and Multipotent Stromal Cellsmentioning
confidence: 99%
“…This computational model did not however propose a specific hypothesis for how environmental factors regulate the initiation and progression of chondrocyte hypertrophy and endochondral ossification, which is central to successful secondary fracture healing. This is clearly a potential limitation of such models, as a number of recent studies have demonstrated that low oxygen conditions can supress hypertrophy and endochondral ossification of chondrogenically primed MSCs (Zhu et al, 2014;Sheehy et al, 2012;Gawlitta et al, 2012;Leijten et al, 2012Leijten et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by in-vitro observations (Zhu et al, 2014;Sheehy et al, 2012;Gawlitta et al, 2012;Leijten et al, 2012Leijten et al, , 2014 our previous in-silico model of MSC differentiation (Burke and Kelly, 2012) was updated to include specific rules for how oxygen levels regulate hypertrophy of chondrocytes. The model was then tested by attempting to simulate fracture healing within a murine tibia in both normal and ischemic limbs, where experimental data was generated to quantify the proportion of hypertrophic cartilage within the calluses of such bones at specific time-points after the initiation of injury.…”
Section: Introductionmentioning
confidence: 99%